Diversity of enterobacteria associated with tomato (Lycopersicum scu-lentum Mill) fruits and greenhouse soils (Scientia Agropecuaria, 2012)
The aim of this study was to evaluate the diversity of Enterobacteriaceae present in soil and tomato fruits from three greenhouses with fertirigation system. These crop systems are an important alternative for production in protected agriculture; however, there is little information about the microbiological quality of the fruit and its relationship with chemical soil characteristics. Soil evaluations consisted of analyzing organic matter content and pH. In the microbiological analysis were isolated and identified enterobacterias organisms from composite samples of soil and fruits at different stages of maturity (0, 50 and 100%). Culture media used was selective, differential and confirmatory testing with VITEK system. Enteropathogenic E. coli (EPEC) and enterotoxigenic E. coli (ETEC) were characterized genotypically, amplifying the lngA and bfpA genes by the technique of polymerase chain reaction (PCR). Diversity index (Simpson (D), Shannon-Wiener (H') and Chao estimator (SChao1) were calculated with the identified species. The species Enterobacter cloacae, Citrobacter freundii and C. brakii had a higher frequency of isolation, EPEC and ETEC were identified in soil samples and in fruits with 100% maturity. In soil, H' indices were positively correlated with the highest organic matter percentages. In fruit, although H 'and D showed less diverse bacterial communities, the isolation of ETEC and Shigella boydii on the fruit surface compromise their safety because they are usually consumed raw.
Keywords: Enterobactericeae; diversity indices; organic matter; soil; tomato.